Respuestas
Respuesta dada por:
29
Hola aquí las respuestas:
(-9)+(-10)-(-11)-(-1)=-19-(-11)-(-1)
=-19+11=-8-(-1)
=-8+1=-7
Espero que te sirva :)
(-9)+(-10)-(-11)-(-1)=-19-(-11)-(-1)
=-19+11=-8-(-1)
=-8+1=-7
Espero que te sirva :)
jgrabiel1202ov4441:
gracias
Respuesta dada por:
28
Ley de signos
+x+=+
+x-=-
-x-=+
-x+=-
Resolucion
(-9)+(-10)-(-11)-(-1)
-9-10+11+1
-19+12
-7
+x+=+
+x-=-
-x-=+
-x+=-
Resolucion
(-9)+(-10)-(-11)-(-1)
-9-10+11+1
-19+12
-7
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años